2021
DOI: 10.1371/journal.pntd.0009909
|View full text |Cite
|
Sign up to set email alerts
|

The burden of zoonoses in Paraguay: A systematic review

Abstract: Introduction Underestimation of zoonoses is exacerbated in low and middle-income countries due mainly to inequalities with serious consequences in healthcare. This is difficult to gauge and reduce the impact of those diseases. Our study focuses on Paraguay, where the livestock industry is one of the major components of the country’s economy. Therefore, the rationale of this study was to develop a case study in Paraguay to estimate the dual impact of zoonotic diseases on both the human health and animal health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Studies that include human and animal data for zoonoses are relatively new (published in the last 20 years, S2 Fig) . We observed an increased number of reports on the dual burden of diseases over the years. Up to date, only three studies have reported zDALYs: on cystic echinococcosis in Morocco [13], 25 zoonoses in Paraguay [11], Taenia solium in Lao PDR [12]. We excluded them from our synthesis since they already contain zDALY values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies that include human and animal data for zoonoses are relatively new (published in the last 20 years, S2 Fig) . We observed an increased number of reports on the dual burden of diseases over the years. Up to date, only three studies have reported zDALYs: on cystic echinococcosis in Morocco [13], 25 zoonoses in Paraguay [11], Taenia solium in Lao PDR [12]. We excluded them from our synthesis since they already contain zDALY values.…”
Section: Discussionmentioning
confidence: 99%
“…The excluded studies with zDALYs were neurocysticercosis in Northern Lao PDR with 3497 zDALYs, cystic echinococcosis in Morocco 18,330 (95% CI 17,775-19,074), and PLOS NEGLECTED TROPICAL DISEASES (bacterial, parasitic, viral, fungal) zoonoses in Paraguay with zDALYs of 62,178 (95% CI 48,696-77,188) (SI 3) [11][12][13]. The percentages attributable to animal burden were 0.4% for Northern Lao PDR, 99% for Morocco, and 69% for Paraguay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimation of the zDALYs will provide a good basis for underestimating the dual burden of zoonoses and address the knowledge gap in this area. We presume that only a few studies have calculated zDALYs for zoonotic diseases (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…These include an additional component called animal loss equivalents, which converts the expected livestock production and local per capita income losses to the equivalent number of human YLD. Nevertheless, this metric has been rarely used in cost-effectiveness analyses of zoonotic diseases (44,45), and only once for schistosomiasis (46).…”
Section: Pillar Ii: Economicsmentioning
confidence: 99%